Is it safe for women with a history of two cesarean deliveries to undergo a vaginal delivery attempt in comparison to patient with a history of one cesarean delivery? - Anna Elisabeth Hentrich; Dörthe Brüggmann; Samira Catharina Hoock; Eileen Deuster; Jakob Thomas Buslowicz; Juliane Bresgen; Nadja Zander; Frank Louwen; Lukas Jennewein (PLoS ONE, 2025)
Introduction Worldwide, numbers of repeat cesarean sections continue to rise. Although there is a multitude of evidence about the safety of a vaginal delivery attempt after one cesarean section, data is scarce regarding the risks of one compared to two prior procedures. This study aims to determine whether vaginal childbirth is less safe and successful for both mother and child in patients with a history of two cesarean sections compared to those with only one. Materials and methods This retrospective cohort study included all patients with a history of one or two prior cesarean deliveries who gave birth at term at Goethe University Frankfurt between 2014 and 2021. Maternal and neonatal morbidity, as well as rates of success for vaginal birth and uterine rupture, were compared between the groups. Results Of the 1967 women studied, 1697 gave birth after one previous cesarean section, while 270 had a history of two prior cesarean sections. There was no significant increase in maternal or fetal morbidity in women with two previous cesarean sections compared to one. However, the success rate of a vaginal delivery was lower in the group with two prior cesareans (27/79, 34.2%) than in the group with one (696/989, 70.3%). The rate of complete uterine rupture was higher in patients with two cesareans who underwent cesarean section after onset of labor (CSAOL-2: 3/89, 3.4%) compared to none in the CSAOL-1 group (0/492, 0.0%; p = 0.004). Maternal and fetal morbidity remained comparable across groups, with NICU admission rates of 11.2% (CSAOL-1) vs. 5.6% (CSAOL-2), and maternal transfusion rates of 0.86% (VBAC-1) vs. 6.45% (VBAC-2). Conclusion In the context of patient autonomy regarding the timing of delivery, offering the patient the choice of different delivery modes after two previous cesareans appears to be safe with respect to maternal and fetal risks. An individualized consultation and thorough counseling are essential, but the opportunity for different delivery options should be respected and supported.